2010
DOI: 10.1261/rna.2228510
|View full text |Cite
|
Sign up to set email alerts
|

Missense suppressor mutations in 16S rRNA reveal the importance of helices h8 and h14 in aminoacyl-tRNA selection

Abstract: The molecular basis of the induced-fit mechanism that determines the fidelity of protein synthesis remains unclear. Here, we isolated mutations in 16S rRNA that increase the rate of miscoding and stop codon read-through. Many of the mutations clustered along interfaces between the 30S shoulder domain and other parts of the ribosome, strongly implicating shoulder movement in the induced-fit mechanism of decoding. The largest subset of mutations mapped to helices h8 and h14. These helices interact with each othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
126
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(138 citation statements)
references
References 51 publications
9
126
2
Order By: Relevance
“…However, other contacts in the decoding com-plex may specifically affect the stringency of decoding, e.g. helix 14 and helix 8 of 16S rRNA that negatively regulate GTP hydrolysis (36), or the interactions between helix 5 and domain 2 of EF-Tu (37). The structural basis for the very strong effect of ribosomal protein L7/12 on the GTPase activity of EF-Tu (38,39) remains to be clarified.…”
Section: Discussionmentioning
confidence: 99%
“…However, other contacts in the decoding com-plex may specifically affect the stringency of decoding, e.g. helix 14 and helix 8 of 16S rRNA that negatively regulate GTP hydrolysis (36), or the interactions between helix 5 and domain 2 of EF-Tu (37). The structural basis for the very strong effect of ribosomal protein L7/12 on the GTPase activity of EF-Tu (38,39) remains to be clarified.…”
Section: Discussionmentioning
confidence: 99%
“…1B,C), and destabilizes bridge B8 allosterically (Fagan et al 2013). All four of these mutations increase both missense and nonsense suppression in vivo (McClory et al 2010). Mutation G886A is located in h27 (Fig.…”
Section: Resultsmentioning
confidence: 95%
“…1A), near the binding sites of several error-promoting antibiotics (Carter et al 2000). While conferring more modest effects on missense and nonsense suppression (McClory et al 2010), G886A was the only mutation to be additionally identified in a screen for translation initiation errors (Qin and Fredrick 2009). Four mutations (C1054U, C1054A, C1200U, and G1491A) are located in or near the A site (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations